2021
DOI: 10.3389/fonc.2021.670051
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Based Analysis of Cell-in-Cell Structures in Esophageal Squamous Cell Carcinoma

Abstract: Cell-in-cell (CIC) structures are defined as the special structures with one or more cells enclosed inside another one. Increasing data indicated that CIC structures were functional surrogates of complicated cell behaviors and prognosis predictor in heterogeneous cancers. However, the CIC structure profiling and its prognostic value have not been reported in human esophageal squamous cell Carcinoma (ESCC). We conducted the analysis of subtyped CIC-based profiling in ESCC using “epithelium-macrophage-leukocyte”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…On one hand, SARS-CoV-2 infection could induce syncytia formation in a way dependent on the presence of a unique bi-arginine motif around the furin cleavage site that dictates cell-cell fusion [ 6 ]. The syncytia resulting from infection-induced cell-cell fusion may actively internalize lymphocytes to form heterotypic cell-in-cell structures [ 6 , 38 ], a pathological phenotype mostly documented in human tumors [ 39 44 ], and genetically controlled by a set of core elements, including adherens junctions, actomyosin and mechanical ring [ 45 49 ]. The formation of cell-in-cell structure frequently leads to the death of the internalized lymphocytes in an acidified lysosome [ 6 , 50 52 ], contributing to lymphopenia which was believed to be a causal factor linked to severe COVID-19 [ 53 – 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, SARS-CoV-2 infection could induce syncytia formation in a way dependent on the presence of a unique bi-arginine motif around the furin cleavage site that dictates cell-cell fusion [ 6 ]. The syncytia resulting from infection-induced cell-cell fusion may actively internalize lymphocytes to form heterotypic cell-in-cell structures [ 6 , 38 ], a pathological phenotype mostly documented in human tumors [ 39 44 ], and genetically controlled by a set of core elements, including adherens junctions, actomyosin and mechanical ring [ 45 49 ]. The formation of cell-in-cell structure frequently leads to the death of the internalized lymphocytes in an acidified lysosome [ 6 , 50 52 ], contributing to lymphopenia which was believed to be a causal factor linked to severe COVID-19 [ 53 – 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently summarized the clinical significance of entotic figures in cancers [7]. Since then, it has been reported that homotypic CIC structures preferentially impact the survival of patients with a late stage of esophageal carcinoma [92]. However, using the published approach, entotic CICs and cannibalistic CICs cannot be distinguished.…”
Section: Entosismentioning
confidence: 99%
“…CICs were most frequently documented in a variety of human tumor tissues [32][33][34][35], where CICs could promote clonal selection and tumor evolution as a mechanism of cell competition [1,36,37], or compromise tumor growth via mediating the in-cell killing by immune cells [38]. Accordingly, CICs and their subtypes had been shown to be an independent prognostic factor for cancer patients [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%